Case Report: Successful Avatrombopag Treatment for Two Cases of Anti-PD-1 Antibody-Induced Acquired Amegakaryocytic Thrombocytopenia - Tu, Xiaofang; Xue, Ali; Wu, Suye; Jin, Mengmeng; Zhao, Pu; Zhang, Hao (Frontiers in Pharmacology, 2022)
Background: Anti-PD-1/PD-L1 immunotherapy has achieved impressive responses in multiple types of malignancies in recent years. However, immune-related adverse events (irAEs) occur and limit their continuous clinical use. Among these irAEs, acquired amegakaryocytic thrombocytopenia (AAT) is rare but often clinically serious, life-threatening and refractory to multiple treatment approaches. Case summary: We reported for the first time the successful treatment of avatrombopag in two cases of anti-PD1 antibody-induced AAT (in particular, one case had progressed to aplastic anemia), which was refractory or intolerant to glucocorticoids, ciclosporin, intravenous immunoglobulin (IVIG), recombinant human thrombopoietin (rh-TPO) and even TPO receptor agonist (TPO-RA) eltrombopag. To date, the two cases manifested as normal platelet counts and are independent of transfusion. Conclusion: Anti-PD1 antibody-induced AAT occurs with low frequency but is often serious and difficult to manage, for which this study proposed vatrombopag as a potential curative and safe approach.